2008
DOI: 10.3414/me0502
|View full text |Cite
|
Sign up to set email alerts
|

Intra-organizational Communication in Healthcare

Abstract: Summary Objectives: Intra-organizational communication is mostly interpersonal. Synchronous interruptive communication is recognized as aprimary source of inefficiency anderror in healthcare, and there is much potential for information and communication technology (ICT) to improve such communication. As recently suggested, however, due to communication failures ICT can also compound medical errors. In this paper we analyze factors that restrict the role of ICT in improving int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 56 publications
1
13
0
2
Order By: Relevance
“…We placed results within a conceptual framework that describes communication space by focusing on how information and communication technology (ICT) can be used to enhance communication in healthcare. 13 Pirnejad maintains that in addition to a communicator, information, and the medium needed to transmit information, three other concepts are equally as important to achieving communication objectives: organizational, cognitive, and social complexity.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We placed results within a conceptual framework that describes communication space by focusing on how information and communication technology (ICT) can be used to enhance communication in healthcare. 13 Pirnejad maintains that in addition to a communicator, information, and the medium needed to transmit information, three other concepts are equally as important to achieving communication objectives: organizational, cognitive, and social complexity.…”
Section: Methodsmentioning
confidence: 99%
“…According to Pirnejad's communication space framework, organizational complexity arises from time and resource constraints imposed by an organization that require healthcare personnel to coordinate their activities with each other to deliver care. 13 Within this complexity, urgent problems must be addressed and unforeseen conflicts resolved, requiring frequent negotiation and adjustment of workflow patterns to meet evolving patient care needs. We found that the workflow misalignment between nurses and physicians, as well as between different physician specialties, contributed to barriers to communication about catheters during rounds.…”
Section: Organizational Complexity Creates Communication Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Il ne s'agit pas uniquement des savoirs qui ont rapport à la profession médicale, mais aussi et surtout de savoir-faire communicationnel qui s'actualise dans les pratiques quotidiennes et les échanges informels Lacoste, 2001). Les TIC en tant qu'outils de stockage et de transmission de données jouent un rôle important dans la constitution et le partage des savoirs et compétences collectifs, et contribuent ainsi au processus d'apprentissage organisationnel, tout en transformant les formes et les modes de collaboration Benghozi, 2001 ;Bouzon, 2004 ;Pirnejad et al, 2008 ;Robey et Boudreau, 1999 ;Safran et al, 1998 ;Vitacca et al, 2009). Les auteurs s'entendent pour dire que les TIC encouragent à la fois la décentralisation (grâce aux outils permettant le travail à distance, comme le courrier électronique et le dossier patient électronique, DPE) et l'intégration (les systèmes informatisés exigent une rationalisation plus accrue et un contrôle plus rigoureux des processus de la création de l'information, de la transmission et de la rétroaction).…”
Section: Thématiques De La Communication Organisationnelle Et Santéunclassified
“…L'intégration des TIC au sein des organisations de santé représente un autre facteur susceptible d'altérer la distribution des rôles, transformer les identités professionnelles et questionner la nature et le sens du travail des acteurs (Alasad, 2002). La question centrale est celle de la distribution du travail entre les acteurs humains et les acteurs technologiques, et de la place de ces derniers au sein des équipes de travail (Pirnejad et al, 2008 ;Safran et al, 1998). L'augmentation de compétences individuelles de certains acteurs grâce à l'utilisation des TIC peut conduire, d'un côté, « à la suppression de certaines tâches, puis de certains métiers » au sein des organisations (Benghozi, 2001, p. 8) Grosjean, 2004 ;Lacoste, 2001 ;Raveyre et Ughetto, 2003 ;Schweyer et al, 2004).…”
Section: Tensions Dans Les Pratiques Et Transformations Des Identitésunclassified